Genetic Forms of Parkinson's Disease - Kim, Christine Y.; Alcalay, Roy N. (Seminars in Neurology, 2017)
One of the greatest advances in Parkinson's disease (PD) research in the past two decades has been a better understanding of PD genetics. Of the many candidate genes investigated, the best studied include LRRK2, SNCA, VPS35, Parkin, PINK1, and DJ1. The authors review the key clinical features of these monogenic forms, as well as for the prevalent risk factor gene, GBA, including the phenotype, clinical course, and treatment response. They also outline areas for future investigation: longitudinal studies of PD's clinical course, the identification of its premotor manifestations, and its specific mechanisms of pathogenicity.
Keywords: Parkinson's disease; genetics; LRRK2; SNCA; VPS35; Parkin; PINK1; DJ1; GBA